2022
DOI: 10.1038/s41598-022-23459-4
|View full text |Cite
|
Sign up to set email alerts
|

Trace minerals source in calf starters interacts with birth weights to affect growth performance

Abstract: The present study was conducted to investigate the effects of partial replacement of inorganic minerals (IM) with trace minerals in advance chelate components form in starter diets for calves of different birth weights on performance, health, and behavior of Holstein calves. Fifty-two calves were assigned to 1 of 4 treatments in a 2 × 2 factorial arrangement with two mineral sources (IM or advanced chelated minerals (ACMS)) and two birth weights (low or normal birth weight; LBW or NBW). Calves were weaned on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In turn, birthweight had a significant effect on live-weight in a mixed model (p < 0.001, Supplementary Table 5). Interestingly a recent study found that as well as starting at a smaller size, calves with a smaller birthweight also grow more slowly (52). A larger study size may allow examination of interactions between the factors examined in this study, but this was not possible with only thirty-one calves.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In turn, birthweight had a significant effect on live-weight in a mixed model (p < 0.001, Supplementary Table 5). Interestingly a recent study found that as well as starting at a smaller size, calves with a smaller birthweight also grow more slowly (52). A larger study size may allow examination of interactions between the factors examined in this study, but this was not possible with only thirty-one calves.…”
Section: Discussionmentioning
confidence: 90%
“…Only one previous study has examined the association of birthweight with milk drinking behaviors and activity variables. It found that calves born at a normal (42.7 ± 2.6 kg) birthweight spent more time drinking milk and had a greater daily standing time than their lighter (34.9 ± 2.4 kg) counterparts (52). In contrast the current study found that calves that were born heavier had fewer lying (Figure 3B) and standing (Supplementary Figure 1) bouts each day, a longer mean standing bout length (Figure 3C) and drank less milk per feed (Figure 5B).…”
Section: Discussionmentioning
confidence: 99%